Quantification of regulatory T cells enables the identification of high-risk breast cancer patients and those at risk of late relapse. - Bates, G; Fox, S; Han, C; Leek, R; Garcia, J; Harris, A; Banham, A (2006)
PURPOSE: To assess the clinical significance of tumor-infiltrating FOXP3-positive regulatory T cells (TR) in breast cancer patients with long-term follow-up. PATIENTS AND METHODS: FOXP3-positive TR were detected by immunohistochemistry with our new, extensively characterized FOXP3 monoclonal antibody, 236A/E7. Numbers of FOXP3-positive lymphocytes in tissue microarray cores from pure ductal carcinoma in situ (DCIS; n = 62), invasive breast cancer (n = 237) or from comparable areas of normal terminal duct lobular breast tissue (n = 10) were determined. A median cutoff of > or = 15 defined patients with high numbers of TR. RESULTS: TR numbers were significantly higher in in situ and invasive breast carcinomas than in normal breast; invasive tumors have significantly higher numbers than DCIS (P = .001). High numbers of FOXP3-positive TR identified patients with DCIS at increased risk of relapse (P = .04) and patients with invasive tumors with both shorter relapse-free (P = .004) and overall survival (P = .007). High TR numbers were present in high-grade tumors (P < or = .001), in patients with lymph node involvement (P = .01), and in estrogen receptor (ER) -negative tumors (P = .001). Importantly, high numbers of TR within ER-positive tumors identified high-risk patients (P = .005). Unlike conventional clinicopathologic factors, high numbers of FOXP3-positive TR can identify patients at risk of relapse after 5 years. CONCLUSION: These findings indicate that quantification of FOXP3-positive TR in breast tumors is valuable for assessing disease prognosis and progression, and that TR are an important therapeutic target for breast cancer. FOXP3-positive TR represent a novel marker for identifying late-relapse patients who may benefit from aromatase therapy after standard tamoxifen treatment.